Identification using higher-order moments restrictions - Philippe Andrade; Filippo Ferroni; Leonardo Melosi (Federal Reserve Bank of Chicago, 2023)
We exploit inequality restrictions on higher-order moments of the distribution of structural shocks to sharpen their identification. We show that these constraints can be treated as necessary conditions and used to shrink the set of admissible rotations. We illustrate the usefulness of this approach showing, by simulations, how it can dramatically improve the identification of monetary policy shocks when combined with widely used sign-restriction schemes. We then apply our methodology to two empirical questions: the effects of monetary policy shocks in the US and the effects of sovereign bonds spreads shocks in the Euro Area. In both cases, using higher-moment restrictions significantly sharpens identification. After a shock to EA governments bonds spreads, monetary policy quickly turns expansionary, corporate borrowing conditions worsen on impact, the real economy and the labor market of the Euro Area contract appreciably, returns on German government bonds fall, likely reflecting investors' flight to quality.
Keywords: C32; E27; E32; 330; Shock identification; skewness; kurtosis; VAR; sign restrictions; shocks to government bonds spreads; monetary shocks; Euro Area